Pengaruh Work Life Balance Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Pada Perumda Tugu Tirta Kota Malang - riska nurul azizah; Achmad Sani Supriyanto (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
Abstract The success or failure of an organization within the company depends on its human resources. When resource management is good, then an organization's goals within the company will be achieved. Therefore, in order for the organization's goals to be met, it is necessary to have employees who have good performance, one of which the company must meet the psychological needs of employees, namely work life balance. This study aims to determine how the direct or indirect effect of work life balance on employee performance through job satisfaction. This study uses a quantitative research type, which emphasizes theoretical testing on variables in numerical research and analysis. The measuring tools of this research are questionnaires and interviews. The object of this research is the employees of PDAM Malang City with a sample of 121 respondents. The sampling technique is simple random sampling. The data analysis test tool in this study used Path Analysis. The results of the study indicate that Work Life Balance has a direct significant effect on job satisfaction due to the significant value at 0.000 <0.05 or less than the specified significant level. Work life balance has a positive effect on employee performance. Based on the results of the study indicate that work life balance has a direct effect on employee performance. Then the results of the first significant test obtained the results of the work life balance variable having a significant effect on the job satisfaction variable. The results of the second significant test showed that job satisfaction had a positive and significant effect on employee performance.